2016
DOI: 10.1007/s10545-016-9942-0
|View full text |Cite
|
Sign up to set email alerts
|

Improving long term outcomes in urea cycle disorders‐report from the Urea Cycle Disorders Consortium

Abstract: The Urea Cycle Disorders Consortium (UCDC) has conducted, beginning in 2006, a longitudinal study (LS) of 8 enzyme deficiencies/transporter defects associated with the urea cycle. These include N-acetylglutamate synthase deficiency (NAGSD); Carbamyl phosphate synthetase 1 deficiency (CPS1D); Ornithine transcarbamylase deficiency (OTCD); Argininosuccinate synthetase deficiency (ASSD) (Citrullinemia); Argininosuccinate lyase deficiency (ASLD) (Argininosuccinic aciduria); Arginase deficiency (ARGD, Argininemia); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 19 publications
4
73
1
1
Order By: Relevance
“…During the neonatal period mortality was found to be 50% in severe cases (4). Similar mortality rates in our patients suggest that early initiation of PD may be an alternative treatment in centers where other treatment options are not available.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…During the neonatal period mortality was found to be 50% in severe cases (4). Similar mortality rates in our patients suggest that early initiation of PD may be an alternative treatment in centers where other treatment options are not available.…”
Section: Discussionsupporting
confidence: 80%
“…PD should be applied as an alternative method to cases where hemodiafiltration is not an option. Although hemodialysis has been considered more effective, some studies have shown that PD is still an effective treatment for hyperammonemic patients (4,5). In our study, PD seemed to be effective when the level of ammonia decreased.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Estimated incidences are 1:35,000 for UCD (Summar et al 2014) and 1:21,000 for OA (Dionisi-Vici et al 2002). Recently, the natural course of the diseases has been described in two large samples (K€ olker et al 2015a;K€ olker et al 2015b;Waisbren et al 2016). These reports highlight that IT-IEM have a major impact on patients' lives: Strict diet, daily intake of medication, the permanent risk of severe metabolic crises, and neurological sequelae are only some of the issues that the growing number of long-term surviving patients and their families face.…”
Section: Introductionmentioning
confidence: 99%
“…Urea cycle disorders result in the accumulation of ammonia causing devastating neurological sequelae in long-term survivors 48. The liver is primarily responsible for ammonia detoxification and mitochondrial ornithine transcarbamylase (OTC, EC 2.1.3.3) catalyses the incorporation of carbamoyl phosphate, involved in ridding the body of excess nitrogen, into the urea cycle.…”
Section: Rare Genetic Metabolic Diseases: Difficult To Treat Conditiomentioning
confidence: 99%